Effects of gallium, indium, and arsenic dose biomarkers and malondialdehyde on zinc protoporphyrin and DNA fragments in optoelectronic workers - Liao, Yen-Hsiung (International Journal of Health, 2015)
Purpose: To investigate whether occupational exposure to gallium, indium, and arsenic may disrupt normal heme production and damage DNA by initiating the release of lipid peroxidation.Methods: 101exposed optoelectronic workers and 65 referents were tested for their whole blood and urine levels of gallium, indium, and arsenic. Plasma malondialdehyde (MDA), blood zinc protophorphyrin (ZPP), and serum DNA fragments were used as indicators of toxic hazards.Results: The MDA, ZPP, and DNA fragment mean levels in the exposed workers were significantly higher than those in the referents. The levels of urine gallium in the exposed workers were significantly correlated with the levels of whole blood ZPP and serum DNA fragments respectively. MDA (the production of lipid peroxidation) may be one of the mechanisms for gallium-related DNA damage in multiple regression models. In addition, gallium was found to have a synergistic effect with arsenic on MDA level that may induce indium to damage DNA in blood cells.Conclusion: ZPP and DNA fragments can be elevated by gallium exposure, and the MDA increase due to combined exposure to gallium and arsenic may play a role in indium-induced DNA damage.